1991
DOI: 10.1159/000210929
|View full text |Cite
|
Sign up to set email alerts
|

Ciclopirox Nail Lacquer 8%: In vivo Penetration into and through Nails and in vitro Effect on Pig Skin

Abstract: This report presents original methods to assess the bioavailability of an antifungal drug from a varnish preparation in finger nails. For the studies with human volunteers a ciclopirox 8 % nail lacquer was used to determine its efficacy in the treatment of onychomycoses. In vivo studies were performed on the fingernails of healthy volunteers by determining the total amount of ciclopirox penetrated per milligram of nail and the partition of the drug in the plate of the nails (technically divided into four layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 7 publications
(9 reference statements)
0
8
0
1
Order By: Relevance
“…The MIC of terbinafine for the major dermatophytes range between 0.001 and 0.06 μ g ml −1 13 . The mean drug concentrations on day 8 after a daily dose of 250 mg terbinafine given for 7 days to eight healthy volunteers were determined in the following tissue compartments: 14 plasma, 1.01 μ g ml −1 ; sebum, 5.18 μ g g −1 ; stratum corneum, 1.63 μ g g −1 ; hair, 1.05 μ g g −1 and nails, 0.52 μ g g −1 . The ratio of MIC to tissue level showed that the concentration of terbinafine in all relevant tissues is 100–1000 times higher than the MIC of the pathogenic dermatophytes.…”
Section: Discussionmentioning
confidence: 99%
“…The MIC of terbinafine for the major dermatophytes range between 0.001 and 0.06 μ g ml −1 13 . The mean drug concentrations on day 8 after a daily dose of 250 mg terbinafine given for 7 days to eight healthy volunteers were determined in the following tissue compartments: 14 plasma, 1.01 μ g ml −1 ; sebum, 5.18 μ g g −1 ; stratum corneum, 1.63 μ g g −1 ; hair, 1.05 μ g g −1 and nails, 0.52 μ g g −1 . The ratio of MIC to tissue level showed that the concentration of terbinafine in all relevant tissues is 100–1000 times higher than the MIC of the pathogenic dermatophytes.…”
Section: Discussionmentioning
confidence: 99%
“…When amorolfine is applied to nail, its penetration is enhanced by pretreatment with DMSO and the penetration is further enhanced if methylene chloride is used as a vehicle for the antifungal in preference to ethanol [217]. Some medicated lacquers are also able to penetrate sufficiently to be of clinical use, particularly if their access is increased by abrading the dorsal surface of the nail plate [218, 219]. The concentration gradient, and hence diffusion, can be increased further by facilitating solution of the reagents, such as miconazole, by lowering the pH [220].…”
Section: Physical Properties Of Nailsmentioning
confidence: 99%
“…A multicenter study of 456 patients demonstrated a 54% clinical response rate for amorolfine nail lacquer; however, patients in this study had no nail bed involvement (27). Ciclopirox, the only FDA-approved topical agent for the treatment of onychomycosis in the United States, achieves drug concentrations in the nail considerably higher than the MIC of ciclopirox for dermatophytes (5). However, poor clinical cure rates have been reported in United States-based studies (Ͻ10% complete cure) (16).…”
mentioning
confidence: 69%